(untitled) (Dialogos, 2018)
Resumo. A Companhia de Jesus foi, sem dúvida, a instituição religiosa mais atuante no território brasileiro no período colonial, portanto, estudá-la significa compreender um pouco da formação cultural brasileira, por meio da catequese e da educação empreendida por aqueles padres. No entanto, sua atuação no Brasil não se dava de forma emancipada da realidade maior que explicava a própria existência do Brasil e daqueles missionários. Nesse sentido, buscou-se neste artigo mostrar a importância de não se perder de vista que a realidade colonial explica-se pelos ditames culturais, políticos e educacionais portugueses. A relação da Companhia de Jesus com a Coroa Portuguesa, a lógica do Padroado Real Português e a relação entre as províncias jesuítas do Brasil e de Portugal são três aspectos apresentados ao longo do artigo como chaves para entender, num contexto mais amplo, a atuação dos jesuítas no Brasil Colônia. Abstract. The Company of Jesus was, without a doubt, the more active religious institution in the Brazilian territory during the colonial period and, therefore, to study its means to understand a little of the Brazilian cultural formation, through the catechesis and of the education undertaken by those priests. However, the performance in Brazil didn’t feel in emancipated way of the largest reality than it explained the own existence of Brazil and of those missionaries. In that sense, it was looked for in this article to show the importance of not losing of view that the colonial reality is explained by the Portuguese cultural, political and education dictates. The relationship of the Company of Jesus with the Portuguese Crown, the logic of the Padroado Portuguese Real and the relationship among the provinces Jesuits from Brazil and of Portugal, they are three aspects presented along the article as keys to understand, in a wider context, the Jesuits’ performance in Colonial Brazil.